Phân cấp đầu tư công khu vực kinh tế Đông Nam Bộ, Việt Nam giai đoạn 2016–2021 - Phạm Thái, Bình; Đặng Văn, Cường; Phạm Hồng, Thắng (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2026)
The Southeast region of Vietnam is a dynamic and fast-growing economic region, with an economic growth rate higher than the national average for over 20 years. However, during the period of 2016–2021, the economic growth rate of the region declined, causing it to lose its leading position in the country. The reasons for this decline are partly due to a decrease in regional public investment, as well as weak and outdated internal and external transportation infrastructure. This article analyzes the current public investment decentralization of the region compared to the national average and proposes some solutions to enhance decentralization and improve the efficiency of public investment disbursement in the region.